A PERSPECTIVE ON GLOBAL FOOD SECURITY-WHERE FROM HERE? - Acram Taji; Tanya Tapingkae (International Journal of Biosciences and Biotechnology, 2012)
A PERSPECTIVE ON GLOBAL FOOD SECURITY-WHERE FROM HERE?